"Direct" 13C Hyperpolarization of 13C‐Acetate by MicroTesla NMR Signal Amplification by Reversible Exchange (SABRE). (14th November 2019) - Gemeinhardt, Max E.; Limbach, Miranda N.; Gebhardt, Thomas R.; Eriksson, Clark W.; Eriksson, Shannon L.; Lindale, Jacob R.; Goodson, Elysia A.; Warren, Warren S.; Chekmenev, Eduard Y.; Goodson, Boyd M.
Abstract: Herein, we demonstrate "direct" 13 C hyperpolarization of 13 C‐acetate via signal amplification by reversible exchange (SABRE). The standard SABRE homogeneous catalyst [Ir‐IMes; [IrCl(COD)(IMes)], (IMes=1, 3‐bis(2, 4, 6‐trimethylphenyl), imidazole‐2‐ylidene; COD=cyclooctadiene)] was first activated in the presence of an auxiliary substrate (pyridine) in alcohol. Following addition of sodium 1‐ 13 C‐acetate, parahydrogen bubbling within a microtesla magnetic field (i.e. under conditions of SABRE in shield enables alignment transfer to heteronuclei, SABRE‐SHEATH) resulted in positive enhancements of up to ≈100‐fold in the 13 C NMR signal compared to thermal equilibrium at 9.4 T. The present results are consistent with a mechanism of "direct" transfer of spin order from parahydrogen to 13 C spins of acetate weakly bound to the catalyst, under conditions of fast exchange with respect to the 13 C acetate resonance, but we find that relaxation dynamics at microtesla fields alter the optimal matching from the traditional SABRE‐SHEATH picture. Further development of this approach could lead to new ways to rapidly, cheaply, and simply hyperpolarize a broad range of substrates (e.g. metabolites with carboxyl groups) for various applications, including biomedical NMR and MRI of cellular and in vivo metabolism. Abstract : Spektren ohne Umschweife : Die Zugabe von metabolisch relevantem 13 C‐Acetat und Parawasserstoff zu Lösungen, die aktivierten Katalysator enthalten, führt zu einer bis zu 100‐fachen Verstärkung der 13 C‐NMR‐Signale bei 9.4 T. Die Hyperpolarisation erfolgt direkt – im Gegensatz zu früheren Ansätzen, die entweder die Synthese von katalysatorbindenden Kompositstrukturen oder die indirekte Weiterleitung der Spinordnung durch andere Spezies erfordert haben.